(3GdehGLgI GdehVhYjI h GdELQGFjI ddLQjeI GdEQgGHjI aj GdbGfhf GdLfGFj GdOhdj h GdOGNdj (B: s (3OQGSI ebGQfI (B/ s - (3eUWai YHOGdYXje MSfs; (3eOMJ YHOGdMdje QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhd GdHMK GdehGLgI GdehVhYjI h GdELQGFjI ddLQjeI GdEQgGHjI aj GdbGfhf GdOhdj h GdOGNdj HOGjI JYQja GdEQgGH h ChLg GdJTGHg Hjf GdXGgQI GdEQgGHjI h ZjQgG ef GdXhGgQ ShGA CcGfJ GdLQjeI efXeI Ch LQjeI SjGSjI Ch Yfa SjGSj h Pdc aj aUd JegjOj(B. (3Ke JfGhdJ GdOQGSI HYO Pdc GdehGLgI GdehVhYjI h GdELQGFjI ddLQjeI Ydi GdeSJhi GdOhdj eJVefB CSGdjH GdecGaMI h CSS GdJYGhf GdOhdj h cPG GdJOGHjQ GdOhdjI GdeJYdb HehGLgI GdLQjeI GdEQgGHjI HeG aj Pdc GdJYGhf GdbVGFj h GdEfGHI GdbVGFjI h JYhjV VMGjG GdEQgGH EVGaI Edi GdGJaGbjGJ GdOhdjI h Pdc aj VhA eG JhUdJ Edjg ef fJGFLs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B552-572s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQjeI GdefXeIs; (3GJaGbjI Lfjas; (3GdLQjeI GdSjGSjIs; (3JYhjV VMGjG GdEQgGHs; (3GdGJaGbjI GdCefjI dOhd GdNdjLs; (3GdJYGhf GdOhdi decGaMI GdEQgGHs; (3GdbQUfI GdHMQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs